2023
DOI: 10.1080/17482631.2023.2172796
|View full text |Cite
|
Sign up to set email alerts
|

The perspectives of patients, nursing students and supervisors on “the caring–learning space” – a synthesis of and further abstraction of previous studies

Abstract: The aim was to describe and gain a greater understanding of the phenomenon “caring-learning space” based on the perspectives of patients, nursing students, and supervisors in clinical practice contexts. A general structure of the phenomenon “caring-learning space” was created based on essential structures from five empirical studies. The analysis is based on a reflective lifeworld research approach (RLR). The “caring-learning” space shows itself in terms of interpersonal relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…It has been found that when the learning space (i.e. interpersonal relationships between the patient in the centre, students, supervisors, and others) is first acknowledged as part of caring, a "caring-learning space" is generated (Holst et al, 2023). Clinical placement anxiety is common in undergraduate nursing students (Simpson & Sawatzky, 2020) and Hilli and Sandvik (2020) have shed light on the fact that the tone of the learning space (i.e.…”
Section: The Learning Spacementioning
confidence: 99%
“…It has been found that when the learning space (i.e. interpersonal relationships between the patient in the centre, students, supervisors, and others) is first acknowledged as part of caring, a "caring-learning space" is generated (Holst et al, 2023). Clinical placement anxiety is common in undergraduate nursing students (Simpson & Sawatzky, 2020) and Hilli and Sandvik (2020) have shed light on the fact that the tone of the learning space (i.e.…”
Section: The Learning Spacementioning
confidence: 99%